Pembelajaran Distribusi Poisson dan Penerapannya dalam Kehidupan Sehari-hari - Baiq Rika Ayu Febrilia (Universitas Syiah Kuala, 2017)
The Mathematical Statistics learning process that integrates theoretical understanding with practice can enhance students' insight into the application of what they have learned (theoretically) in the classroom into everyday life. Theoretical learning will create a boring learning environment. Students have no idea of the use of the theory they have acquired. Based on these reasons, it is necessary to design a learning activity that can help students to apply their understanding of the theory they have acquired. This research describes the learning process of Poisson distribution which is designed by adding its application activity in a problem. This learning is part of the Mathematical Statistics course at teacher education program. This research was conducted for four weeks on Short Semester. One week consists of three meetings. This research involves seven students of IKIP Mataram majoring in Mathematics Education who have taken the Mathematics Statistics course and repeat the lecture in Short Semester. The data collected were obtained from interview video, students assignment sheet, accompaniment video data analysis process using Poisson distribution, and student worksheets in Microsoft Excel. Students are required to conduct visitor surveys at several education centers and shopping centers. After that, we guide them to process and analyze data using Poisson distribution. The discussion section highlights the description of the lessons and the development of students' understanding